10.61533 STUDI PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP PENDAPATAN KAPITASI DAN NON-KAPITASI PASIEN BPJS PADA MEDICARE CLINIC SUNGAILIAT KABUPATEN BANGKA - Sri Melati Ningsih; Burhanuddin Bani; Mohamad Makrus (Jurnal Ilmiah Niaga Bisnis Elektronik, 2025)
This study aims to examine the implementation of an Accounting Information System (AIS) in managing capitated and non-capitated revenue from BPJS patients at Medicare Clinic Sungailiat, Bangka Regency. Capitated revenue refers to fixed payments received based on the number of registered BPJS participants, while non-capitated revenue stems from additional services not covered under the capitation scheme. Using a qualitative descriptive approach, the research employs observation, interviews, and documentation to assess the effectiveness of AIS in recording, reporting, and controlling these revenue streams. The findings reveal that AIS has significantly improved the accuracy, efficiency, and transparency of financial management at the clinic. It also supports compliance with BPJS Health regulations and national accounting standards. However, challenges remain, including limited staff proficiency in using the system and the lack of integration across service units. The study recommends capacity-building initiatives, system integration, and regular audits to enhance decision-making and financial accountability.